Afiksasi Verba Bahasa Kutai - Lilik Rita Lindayani (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
The objective of this research is to analyze about Verbs Affixation of Kutainese Language. Affixation on the verb is analyzed based on the procces. The data obtained through verbal and artificial data. The data in the form of a written language and folklate were also used as supporting data. The method used in this research was descriptive qualitative method. The data was described by emphasise on data qualities (characteristics of the natural data) in accordance with understanding and naturalness descriptive data obstained in the field. The finding showed that in Kutainese language all types of affixs may establish verbs, except the suffix {-an}. Affixation of Kutainese language can be distiguished on the prefix, sufix, infix, confix, simulfix (affix cambination). Key words: verbs, affixation, Kutainese language